THE RELATIONSHIP OF LEADERSHIP STYLE OF THE HEAD OF THE ROOM WITH NURSE'S WORK MOTIVATION IN THE TREATMENT ROOM - Nurfadillah Nurfadillah (Sean Institute, 2021)
This study aims to determine the relationship between the leadership style of the head of the room with the work motivation of nurses in the treatment room of the Sheikh Yusuf Hospital Kab. This research was conducted at the Regional General Hospital of Sheikh Yusuf Gowa. The population in this study were all nurses who served in the surgical, internal and pediatric care rooms at Syekh Yusuf Gowa Hospital. From the results of the study, it can be seen that the leadership style used by the head of the room is democratic and the work motivation of nurses is high. It is recommended for the Sheikh Yusuf hospital that the heads of the treatment rooms can apply a democratic leadership style to get high work motivation for nurses.